2019
DOI: 10.1177/1091581819849833
|View full text |Cite
|
Sign up to set email alerts
|

The Role of the Human Microbiome in Chemical Toxicity

Abstract: There is overwhelming evidence that the microbiome must be considered when evaluating the toxicity of chemicals. Disruption of the normal microbial flora is a known effect of toxic exposure, and these disruptions may lead to human health effects. In addition, the biotransformation of numerous compounds has been shown to be dependent on microbial enzymes, with the potential for different host health outcomes resulting from variations in the microbiome. Evidence suggests that such metabolism of environmental che… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(24 citation statements)
references
References 154 publications
(169 reference statements)
0
24
0
Order By: Relevance
“…Evidence is accumulating on the efficient conversion of acetylated forms of DON to DON by intestinal microbiota. [ 9,10,19 ] However, so far, to the best of our knowledge, kinetics of this process by microbiota from different host species have not been defined. Hence the present study aimed to assess the interspecies deacetylation kinetic constants for conversion of the major food‐borne acetyl‐DONs, i.e., 3‐Ac‐DON and 15‐Ac‐DON.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence is accumulating on the efficient conversion of acetylated forms of DON to DON by intestinal microbiota. [ 9,10,19 ] However, so far, to the best of our knowledge, kinetics of this process by microbiota from different host species have not been defined. Hence the present study aimed to assess the interspecies deacetylation kinetic constants for conversion of the major food‐borne acetyl‐DONs, i.e., 3‐Ac‐DON and 15‐Ac‐DON.…”
Section: Discussionmentioning
confidence: 99%
“…In vitro and in vivo studies have demonstrated that gut microbiota can modulate the toxicity of arsenic via direct metabolism of arsenic (including oxidative methylation and glutathione conjugation), and this process also increases the bioavailability of arsenic 65 , 66 . In addition to arsenic, it has been proven that gut microbiota can metabolize other heavy metals such as mercury and chromium, and thus change their bioavailability 67 .…”
Section: Nonnegligible Role Of Gut Microbiota In Precision Medicine: mentioning
confidence: 99%
“…These occur in the liver and kidney, but various biotransformation reactions in the intestine can also be carried out through the microbiota. In this context, there is evidence at the preclinical level in cell cultures and in animal models that the microbiota performs various chemical reactions that can modify the toxicity of heavy metals; since heavy metals when distributed in the body can be concentrated in the bile and subsequently enter the enterohepatic circuit, or during their journey through the gastrointestinal system they may be susceptible to being biotransformed by the microbiota enzymes to less or more compounds toxic to the individual and even to the microbiota itself [35,36]. This is a new issue that is changing the approach to toxicokinetics and toxicodynamics of heavy metals and other environmental toxins.…”
Section: Toxicokinetics and Heavy Metal Toxicodynamicsmentioning
confidence: 99%